Study creating and cloning hairy root lines in Talinum paniculatum plants - Thi Nhu Trang, Vu; Hoang Mau, Chu (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
Talinum paniculatum Gaertn. contains flavonoid and saponins that have strong antioxidant properties, which are used to treat a number of conditions such as inflammation, allergies, stomach ulcers, ... However, the amount of flavonoid synthesized naturally in Talinum paniculatum plants is very low (about 0.897 mg /g fresh leaves). Therefore a method has been proposed for enhancing flavonoid content in Talinum paniculatum plants by applying tissue culture technique to produce the hairy roots to enhance biomass. This study present the results of optimization of the gene transfer process to create the hairy root lines through Agrobacterium rhizogenes ( A. rhizogenes ) in Talinum paniculatum plants. Of the three types of materials that infect by A. rhizogenes (cotyledon, stem, leaf tissue), leaf tissue is a suitable material for transforming and inducing hairy roots. Density of bacteria corresponding to OD600 value=0.6; concentration AS 100 μmol/l; Infection time of 10 minutes; 2 days of co-culture; cefotaxime concentrations of 500 mg/l are suitable conditions for inducing hairy roots from leaf tissue. In state of the liquid MS medium without growth regulator, shaking culture conditions are suitable for hairy roots growth. The test result of presence of rolC gene by PCR and the absence of the virD2 gene asserted that 5 lines of hairy roots were produced from Talinum paniculatum plants.